1997
DOI: 10.1002/chem.19970030717
|View full text |Cite
|
Sign up to set email alerts
|

Large Quadratic Hyperpolarizabilities with Donor–Acceptor Polyenes Exhibiting Optimum Bond Length Alternation: Correlation Between Structure and Hyperpolarizability

Abstract: Donor-acceptor polyenes of various lengths, and that combine aromatic electron-donating moieties with powerful heterocyclic electron-withdrawing terminal groups, have been synthesized and characterized as efficient nonlinear optical (NLO) chromophores. Their linear and nonlinear optical properties have been investigated, and variations in these properties have been related to ground-state polarization (dipole p ) and structure. In particular, unprecedented quadratic hyperpolarizabilities (p) have been achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
303
1
6

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(321 citation statements)
references
References 50 publications
10
303
1
6
Order By: Relevance
“…We find good evidence of this in the research of nonlinear optical (NLO) materials, where several structure-property relations are highlighted (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and where computational modeling has advanced quite far (13). One such important structure-property relation for NLO materials is the relation between the first hyperpolarizability and the bond-length alternation (BLA) parameter for molecules that can exist in resonance between the two, neutral or charge-separated (zwitterionic) forms (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The BLA parameter has been defined as the difference between the average single and double bond lengths in the conjugation pathway (14).…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…We find good evidence of this in the research of nonlinear optical (NLO) materials, where several structure-property relations are highlighted (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and where computational modeling has advanced quite far (13). One such important structure-property relation for NLO materials is the relation between the first hyperpolarizability and the bond-length alternation (BLA) parameter for molecules that can exist in resonance between the two, neutral or charge-separated (zwitterionic) forms (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The BLA parameter has been defined as the difference between the average single and double bond lengths in the conjugation pathway (14).…”
mentioning
confidence: 62%
“…It has been shown that with increasing field strength and increasing solvent polarity, the BLA parameter decreases and in some cases changes sign with a cyanine-like structure corresponding to a BLA parameter equal to zero (14,17). The BLA parameter has therefore been proposed to be a structural parameter to be tuned for optimizing nonlinear optical response because this directly quantifies the ground state polarization (2,10,11). For a particular molecule, the BLA parameter can be tuned internally by varying the strengths of the donor and acceptor groups or by altering the conjugation length, and externally by using electric fields or solvents of different polarity (6, 9, 14-16, 18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,[7][8][9] There have been recent significant advances in the development of specialized chromophores and dyes for biophotonic imaging techniques. Of particular interest are dyes whose optical properties (particularly, fluorescence quantum yield) are modified by binding to biomolecular environments, as these chromophores offer the ability to selectively image specific binding targets.…”
Section: Introductionmentioning
confidence: 99%
“…For linear chain oligomers it has been known that the band gap, nonlinear optical (NLO) properties, excited states, etc. are BLA-dependent [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%